Engineering Robustness of Microbial Cell Factories. Issue 10 (18th September 2017) - Gong, Zhiwei; Nielsen, Jens; Zhou, Yongjin J.
Abstract : Metabolic engineering and synthetic biology offer great prospects in developing microbial cell factories capable of converting renewable feedstocks into fuels, chemicals, food ingredients, and pharmaceuticals. However, prohibitively low production rate and mass concentration remain the major hurdles in industrial processes even though the biosynthetic pathways are comprehensively optimized. These limitations are caused by a variety of factors unamenable for host cell survival, such as harsh industrial conditions, fermentation inhibitors from biomass hydrolysates, and toxic compounds including metabolic intermediates and valuable target products. Therefore, engineered microbes with robust phenotypes is essential for achieving higher yield and productivity. In this review, the recent advances in engineering robustness and tolerance of cell factories is described to cope with these issues and briefly introduce novel strategies with great potential to enhance the robustness of cell factories, including metabolic pathway balancing, transporter engineering, and adaptive laboratory evolution. This review also highlights the integration of advanced systems and synthetic biology principles toward engineering the harmony of overall cell function, more than the specific pathways or enzymes. Abstract : The efficiency of microbial cell factory is always hampered by harsh fermentation conditions, inhibitors, or toxic products. In this review, the authors describe recent advances in engineering cellular robustness and tolerance to improve the performance of microbial cell factories. The work also highlights the integration of advanced systems and synthetic biology toward engineering the harmony of overall cell function.